GIS Approach to Determine Suitability of Trees for Afforestation (International Journal of Innovative Research in Computer Science & Technology, 2021)
9.4 million trees across forest areas in  India have been lost to development projects over the  period of past 4 years (2015-16 to 2018-19). This is  according to the Union ministry of environment, forests  and climate change (MoEFCC). Afforestation refers to  the effort to plant trees in barren lands to create a forest.  Planting trees, sowing seeds in a barren land so as to  create a forest. It is very vital as it helps to keep in check  the over usage of natural resources by providing an  alternative source. Planting trees is always beneficial to  the environment regardless of the habitat.
Keywords: Geographical Information System; Weighted Sum; Rasters; Landscape Model